We, the People and the World: American Liberalism’s Troubled Relationship with International Law - Dickson, Tiphaine L. (Sociološki pregled, 2019)
The emergence of law in society and the role that it occupies are fundamental to any account of liberal theory. As difficult as it is to secure agreement as to the ontological nature and epistemic requirements of law on a liberal view, the challenges that confront the liberal idea of law increase exponentially when considered as an international phenomenon. It is when justice is conceived of beyond the territorial borders of the modern sovereign state that problems emerge with the greatest acuity for liberals, as there is no international tribunal to genuinely and definitively adjudicate claims. Contrary to the ideals of many liberals, power still essentially reigns supreme among nations, a reality that sits uncomfortably with legalistic liberalism itself.
Keywords: Liberalism; international law; sovereignty; humanitarian intervention; Nuremberg